Epigenetic and genetic approach to the transmissibility of dental characteristics in twins: report of two cases - Martins, Ronald Jefferson [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Costa, Patrícia Aparecida; Arruda, Alan Carlos Braga; Amoroso, Andressa Paschoal (National Library of Serbia, 2011)
Transmissibility of dental and jaw characteristics is strongly influenced by environmental factors during the years of extra uterine life when odontogenesis occurs. Through biochemical factors, such as enzymes, proteins, hormones and other mediators, genes are activated or silenced to suit the cell or organism to its environment. These changes are not transmitted to our descendants, because of that, these factors are called epigenetic. Among the most cited epigenetic factors are food, pollution, drugs and exercise. The objective of this study was to assess the transmissibility of dental characteristics in two pairs of twins. In one case, 13-year-old boys had the same basic dental and jaw characteristics with prolonged retention of the second upper deciduous molars and the presence of permanent successors. In the other case, 14-year-old boys had prolonged retention of lower deciduous second molars and absence of permanent successors, but only one of them had the germs of third lower molars. The phenotypic difference in the dentition of twins from clinical case 2 could be due to epigenetic factors, showing the absence of genetic determinism in the transmissibility of dental characteristics.
Keywords: Epigenesis; Genetic; Genetics; DNA methylation; Twins